Tips for Reporting Musculoskeletal Imaging Studies: Lessons Learned - Griffith, James Francis (Seminars in Musculoskeletal Radiology, 2021)
This paper is designed to be read by radiological trainees who are starting out with reporting musculoskeletal imaging studies. Based on the author's experience of over 25 years, it provides tips on how to report musculoskeletal imaging succinctly and effectively using a prose style report.
Keywords: musculoskeletal; imaging; report; radiology; MRI; CT; ultrasound